Faktor-Faktor yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan pada Perusahaan Infrastruktur, Utilitas, dan Transportasi yang terdaftar di Indeks Saham Syariah Indonesia (ISSI)Periode 2013-2015 - Sari, Ranti Puspita; , Dr. Zulfikar, SE, M.Si (2017)
This study aimed to analyze the factors that affect the timeliness of financial reporting on the company Infrastructure Sector, Utilities, and Transport Listed in Index Saham Syariah Indonesia (ISSI) period 2013-2015. The examined factors of this research are auditor opinion, public accounting firm size, profitability, firms size, liquidity, and leverage as independent variables while timeliness as dependent variable. The sample used in this study were 55 the company Infrastructure Sector, Utilities, and Transport Listed in Index Saham Syariah Indonesia (ISSI) period 2013-205. The data used in this research is secondary data selected based on purposive sampling method. These factors were then tested using logistic regression analysis with a significant level of 5 %. These results indicate that the firms size have an influence on the timeliness of corporate financial reporting, while firm auditor opinion, public accounting firm size, profitability, liquidity, and leverage has no effect on the timeliness of corporate financial reporting on the company Infrastructure Sector, Utilities, and Transport Listed in Index Saham Syariah Indonesia (ISSI).